Factors Associated With Chronic Energy Deficiency (Ced) In Adolescent Girls Aged 10-19 In Jambi Province - Lione Alfionita Hafidz; Dwi Noerjoedianto; Muhammad Ridwan; Muhammad Syukri; Kasyani Kasyani (CV. AFDIFAL MAJU BERKAH, 2026)
Chronic Energy Deficiency (CED) is a critical nutritional issue among Indonesian adolescent girls. In Jambi Province, its prevalence shows a fluctuating upward trend, requiring a thorough analysis of risk determinants. This study aimed to determine CED prevalence and analyze its association with macronutrient intake frequency, infectious diseases, hygiene behavior, physical activity, and family size. This quantitative study used a cross-sectional design with 2023 Indonesian Health Survey (SKI) secondary data. The sample consisted of 1,082 adolescent girls (10–19 years) in Jambi Province. Data were analyzed using Chi-square and Cox Regression to identify dominant factors and Prevalence Ratios (PR). CED prevalence was remarkably high at 56.1%, predominantly in the 15–19 age group (51.6%). Nutritional patterns showed infrequent consumption of carbohydrates (51.7%), fats (66.0%), and proteins (58.3%). While most respondents reported good hygiene and no infection history, bivariate analysis showed no significant association with CED. However, multivariate analysis identified light physical activity as the dominant factor significantly associated with CED risk (p-value: 0.045; PR: 1.45; 95% CI: 1.00–2.08). Physical activity is the primary determinant of CED among adolescent girls in Jambi. These findings highlight the urgency for comprehensive nutritional interventions focusing on energy balance and dietary quality.